The standing of vocational education and the occupations it serves : current concerns and strategies for enhancing that standing - Billett, Stephen [Herausgeber]; Stalder, Barbara E. [Herausgeber]; Aarkrog, Vibe [Herausgeber]; Choy, Sarojni [Herausgeber]; Hodge, Steven [Herausgeber]; Anh Hai Le [Herausgeber] (Springer, 2022)
"This book addresses what is, perhaps, the single most important issue for vocational education; its relatively low standing in an era of high aspiration. The work explores the nature, extent and consequences for an educational sector that whilst having an increasingly important role in contemporary societies is seen to be of low standing across both countries with developed and developing economies. Some of the standing is associated with the occupation it serves and this is highlighted in an era of high aspiration by young people and their parents. The consequences are far-reaching. This includes how governments and community view and support vocational education, parents and familiars advise about participation in it and young people’s decision-making associated with their post-school pathways. More than describing this problem, the focus of this collection is how this issue can be redressed through the actions of supra-government agencies, governments, schools in tertiary education institutions, industry and professional bodies and employers. It sets out the quality and extent of societal sentiments in shaping how vocational education and the occupation it serves are projected, across countries, continents and cultures, and offers a range of perspectives and contributions from scholars on how this issue might be redressed. These contributions are drawn together and synthesised into sets of propositions, practices and approaches directed towards governments, schooling and tertiary education institutions, educators, researchers, industry and professional bodies and employers. In this way, the book seeks to provide an authoritative, seminal, comprehensive and central text to understand and respond to this central issue for vocational education." (Publisher)
E-Book für BIBB-Mitarbeitende über die Bibliothek erhältlich.
Keywords: S 1 Stufen der Berufsbildung; G 2.3 Wandel von Arbeit & Wirtschaft; I 2.2.1 Westeuropa; I 2.2.2 Osteuropa; I 2.3.4 Asien; I 2.3.5 Australien, Ozeanien; 370; Berufsbildung; Berufsausbildung; Sozialprestige; Attraktivität; Berufswahl; Internationaler Vergleich; Australien; Bundesrepublik Deutschland; Dänemark; Finnland; Frankreich; Indien; Norwegen; Rumänien; Schweiz; Vietnam